KAJIAN LITERATUR KURIKULUM PENDIDIKAN IPA: KONTEN IPA PERGURUAN TINGGI ABAD 21 - Fatkhurrohman, Mukhammad Aji; Hamidah, Ida; Yustiana, Yusi Riksa; Rochintaniawati, Diana (Jurnal Pendidikan Ilmu Pengetahuan Alam (JP-IPA), 2023)
Higher education has a very important role and is expected to be able to produce quality graduates to be able to bring the Indonesian nation to a more advanced direction and ready to answer challenges in the 21st century. The purpose of this study is to describe of how the content of higher education science in the 21st century. The research method used is SLR (Systematic Literature Review) with narrative review. The results show that the content of Higher Education Science in the 21st Century is designed by referring to the scope of Science, Learning Content Standards on SNPT,Â andÂ the 21st Century Learning Framework